KEPATUHAN PAJAK, NORMA SOSIAL MASYARAKAT , PENEGAKAN HUKUM, DAN MORAL PAJAK PERUSAHAAN AGRO PADA BURSA EFEK DI INDONESIA - Jap, Yustina Peniyanti (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
Indonesian annual tax receipts in the government budgets are mostly below 100%, indicating that the tax role in fiscal policy has not been satisfactory. Economic growth based on the fiscal policies applied by the Indonesian government is not followed by tax payments by the Indonesians. It indicates that not all of the tax payers complies their payment according to the tax due from the regulations. The purpose of the study is to examine and analyze the effect of social norm, taxation, law enforcement, and moral taxpayer to the tax compliance of agro sector public companies listed on the Indonesia Stock Exchange. The method used is descriptive quantitative and linear regression, using primary data from the responses to questionnaires involving 14 company respondent. Hypothesis testing is done by t-test and F-test using SPSS software. The result of the analysis and discussion demonstrate that social norms taxpayers, law enforcement and taxpayer Moral partially and simultaneously have a positive and significant effect on Compliance on paying taxes. The result also prove that in order to improve taxpayer compliance government can not rely solely on law emforcement (inspections and fines), but there are many other factors that also contribute to determine tax compliance such as social norms and taxpayersmoral which is a reflection of public perception of the administration of taxation and government.  Keywords: tax compliance, social norm, law enforcement, taxpayers moral.